Arbetsbehovet och på det påverkande faktorer vid radmyllning och kombinerad radmyllning och sådd - Pehkonen, Aarne (Agricultural and Food Science, 1971)
According to the work studies carried out in the years 1968—70, the average labour requirement in fertilizer placement was 51 min/ha and in combine drilling 70 min/ha. In both jobs the effective time, driving with coulters down, was below 50 % of the field working time. The speed has obviously affected the output of the work, more than the working width of the implemens. The driver has apparently influenced the selection of the speed. In addition to the driving time, the time required for turning and filling has influenced the output of the work. These three make up about 80 % of the field working time. The speed to turn a machine combination was not found to be dependent on the way the implement was pulled by the tractor (tractor mounted or trailed). On the other hand the skill of the driver affects the turning time. The work input of a worker influences the filling speed. In filling, team work (2 —3 persons) has increased the labour consumption (min/100 kg/man) on an average from 1.61 to 2.54 min. Time per a quantity in filling decreases while the quantities increase. This is due to the diminishing of the relative share of the start-up and shut-down times. Acording to the studies, it is possible to increase the work output in fertilizer placement and combine drilling mainly in the folloving ways: decrease the labour consumption of effective time by increasing the working width and/or speed of the machine combination, and/or increase the relative share of the effective time in the total field time by reducing unproductive times.